BANG BOO CHUANG YIN MUAN TAI: A CREATIVE DANCE INSPIRED BY FOLKWAYS AND BANG BOO PLAY OF THE THAI DUM ETHNICS - HONGYEESIBED, SARIYA; CHITKUL, KRAILAS (Journal of Suan Sunandha Arts and Culture, 2023)
This creative research was conducted to create a performance from study of history, lifestyle and culture of Tai Dam ethnic group, Ban Na Pa Nat, Khao Kaew Subdistrict, Chiang Khan District, Loei Province, and to disseminate the “bang boo” culture, a tribal musical instrument of the Tai Dam ethnic group. The study used qualitative research method to collect data from academic documents, related research, interviews, and from various information media, to analyze and synthesize until the body of knowledge to the creative design of the performance, called “Bang Boo Chuang Yin Muan Tai”. The results showed that Tai Dam ethnic group Ban Na Pa Nad, Khao Kaeo Subdistrict, Chiang Khan District, Loei Province, migrated from Sipsong Chutai Province during the reign of King Rama V. They have a distinctive identity in terms of costume, dance and music, especially the long-standing bamboo musical instrument known as “Bang Boo”. Has become less popular and is at eminent risk of becoming lost from the record. The research team was inspired by those ideas to represent the identity of “Bang Boo” in form of contemporary Isan dance that still maintains and preserves the identity of the Tai Dam ethnic group. The performance is divided into 3 parts: 1) the way of life of the Tai Dam people, 2) the identity of the Bang Bu musical instrument, and 3) the gathering of the Tai Dam ethnic groups. The dance movement and patterns are a combination of traditional dance postures in the Sae Pang ceremony of the Tai Dam people and using the style of contemporary Isan dance techniques. The costume design retains its original form and is partially modified without affecting the traditional dress codes of the Tai Dam people. The music used in the performance is a newly created from Isan melody. Finally, the props, there are 4 types of Bang Boo namely Bang Boo Toi Pu, Bang Boo Toi Mear, Bang Boo Kaa-taey and Bang Boo Lai. This show can be used for promoting tourism in events as appropriate.